Implications of normalized difference vegetation index on biomass feed production potential for livestock in crop-livestock systems in South-western Ethiopia - Guja, A.A.; Mekasha, Yoseph; Kassa, H.; Tana, T. (2019)
The study was initiated to quantify biomass feed supply for livestock using NDVI (Normalized Difference Vegetation Index) in crop-livestock systems in the southwestern Ethiopia. This was achieved through characterization natural resource-based, smallholder mixed crop-livestock production systems discretely subdividing in different AEZs (Agro-ecological zones) into LULC (Land Use Land Cover) class. The field survey was conducted in seven districts within selected sub-regions in two administrative zones. Factors influencing livestock feed available, accessible and workable factors on land use type were superimposed. The available annual total livestock feed production was 92% from grazing sources and 8% from food crop products. However, monthly livestock DM (Dry Matter) balance from all available sources were showed negative balance compared to estimated livestock requirements in most of the sub-regions. Although the total annual balance surplus. A strong correlation association was evidenced between biomass available feed nutrients, estimated livestock requirements and the productivity performances of livestock. Thus, adhering to a place appropriate management strategy could be vital govern consistency. The results of analysis essentially implicated the potential of feed production from available biomass base which would by far maintain the consistence of livestock production performance, which in turn can contribute livelihood strategy of smallholder producer.